Emerging startup studios in Portugal : organizational characteristics of Portuguese startup studios - Bastos, João Nuno Pereira (2019)
There is an emerging trend in the entrepreneurial landscape which promises to become revolutionary: Startup Studios. This emerging incubation model is generally characterized by the development of internally generated ideas and the creation of its own cohort of startups, supported by internal resources and a multidisciplinary team. Despite the Startup Studio model being already highly implemented in bigger and more developed entrepreneurial ecosystems, the infancy of the underlying concept and the diverging way each Startup Studio organizes itself, combined with the lack of academic research on this topic leaves an unclear definition of the Startup Studio concept. This thesis aims to clarify the definition of the Startup Studio concept and its characteristics. Moreover, it focuses on the implementation of the studio incubator model in smaller and emerging entrepreneurial ecosystems to understand if it can be a viable alternative to foster innovation and prompt economic development. Thus, two case studies of Startup Studios in Portugal were conducted. The findings of this analysis revealed that elements like funding, type of founders and exit strategy will be context specific, differing from Startup Studios in bigger economies. However, elements like ideation process, equity distribution, operations and team set up of Startup Studios in smaller and emerging entrepreneurial ecosystem will be like the ones found in more developed entrepreneurial ecosystem. Based on this evidence, a definition for the Startup Studios is suggested as well as the proposition of the possible implication of the studio incubator model in smaller economies.